(untitled) (International Conference on Economics, Business, and Management Research (ICEBMR), 2024)
The purpose of this study was to determine the development of Micro, Small and Medium Enterprises (MSMEs) and their influence on economic growth. This study used a quantitative approach with a simple linear regression analysis model. The data used was panel data obtained from Bank Indonesia, Central Statistics Agency, Bappenas using period data from 2018-2020. The results showed that MSMEs have a positive and significant effect on economic growth. This article focuses on Bengkulu Province, which perhaps has not been studied much in previous research. Many studies on MSMEs and economic growth may have been conducted at the national level or in other regions, but research specifically in Bengkulu adds new and contextual data that is important for regional understanding.